2018
DOI: 10.1038/s41563-018-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional itinerant ferromagnetism in atomically thin Fe3GeTe2

Abstract: Discoveries of intrinsic two-dimensional (2D) ferromagnetism in van der Waals (vdW) crystals provide an interesting arena for studying fundamental 2D magnetism and devices that employ localized spins. However, an exfoliable vdW material that exhibits intrinsic 2D itinerant magnetism remains elusive. Here we demonstrate that FeGeTe (FGT), an exfoliable vdW magnet, exhibits robust 2D ferromagnetism with strong perpendicular anisotropy when thinned down to a monolayer. Layer-number-dependent studies reveal a cros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

62
1,116
6
16

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,251 publications
(1,200 citation statements)
references
References 33 publications
62
1,116
6
16
Order By: Relevance
“…The FG2T resistivity corresponds to metallic behavior, as predicted earlier by DFT. Similar resistivity values at 300 K have been reported for FGT (648 and 440 μΩ cm[9b]) and Fe 5− x GeTe 2 (300 μΩ cm[14b]). FG2T is therefore a FM metal, as predicted by DFT.…”
supporting
confidence: 82%
“…The FG2T resistivity corresponds to metallic behavior, as predicted earlier by DFT. Similar resistivity values at 300 K have been reported for FGT (648 and 440 μΩ cm[9b]) and Fe 5− x GeTe 2 (300 μΩ cm[14b]). FG2T is therefore a FM metal, as predicted by DFT.…”
supporting
confidence: 82%
“…A, Crystal structure of Fe 3 GeTe 2 (FGT) . B, Polar RMCD signal for a monolayer FGT at several fixed temperatures . C, Thickness‐temperature phase diagram for three distinct magnetic states: paramagnetic (PM), single domain ferromagnetic (FM1) and labyrinthine domain ferromagnet (FM2) .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
“…The group of Xu et al has reported intrinsic itinerant magnetism in exfoliated 2D-FGT, by means of low-temperature electrical transport and RMCD measurements. 81 Figure 4B shows the polar RMCD signal as a function of magnetic field for monolayer FGT at several temperatures. With increasing temperature, the hysteresis shrinks accordingly and disappears at 130 K, indicating the Curie temperature for monolayer FGT.…”
Section: Fe-based Vdw Magnetsmentioning
confidence: 99%
See 2 more Smart Citations